Management of Breech Presentation: A Comparison of Four National Evidence-Based Guidelines - Tsakiridis, Ioannis; Mamopoulos, Apostolos; Athanasiadis, Apostolos; Dagklis, Themistoklis (American Journal of Perinatology, 2019)
Objective The management of breech presentation may improve perinatal outcomes. The aim of this study was to synthesize and compare published evidence of four national guidelines on breech presentation.Study Design A descriptive review of four recently published national guidelines on breech presentation and external cephalic version (ECV) was conducted: Royal College of Obstetricians and Gynaecologists guideline on “External Cephalic Version and Reducing the Incidence of Term Breech Presentation” and “Management of Breech Presentation”, American College of Obstetricians and Gynecologists guideline on “External Cephalic Version” and “Mode of Term Singleton Breech Delivery,” Society of Obstetricians and Gynaecologists of Canada guideline on “Vaginal Delivery of Breech Presentation” and the Royal Australian and New Zealand College of Obstetricians and Gynaecologists guideline on “Management of breech presentation at term.”Results Regarding ECV, there is no recommendation by the SOGC, whereas all other national guidelines recommend this technique. Regarding breech vaginal delivery, there are limited recommendations by the ACOG, whereas all other guidelines provide similar recommendations. The RANZCOG makes no special recommendations on the intrapartum period.Conclusion The differences among national guidelines point out the need for the adoption of an international consensus on the management of breech presentation.
Keywords: breech delivery; external cephalic version; management; comparison; guidelines